Nursing Care with Effective Cough Training for Asthma Patients with Ineffective Airway Clearance at RSUD Dr. Wahidin Sudiro Husodo, Mojokerto: A Case Study - Agustin, Nurul (Jurnal Penelitian, 2025)
Background: Asthma is a chronic respiratory disease characterized by inflammation of the airways, causing difficulty breathing and symptoms such as shortness of breath, coughing, and wheezing. One of the primary problems for asthma sufferers is ineffective airway clearance, often caused by the accumulation of mucus. This condition can worsen asthma symptoms and increase the risk of attacks. The method employed is descriptive, utilizing a case study approach to nursing care involving two respondents. Data collection techniques included interviews, observation, and documentation of activities carried out, including assessment, nursing diagnosis, nursing intervention, implementation, and evaluation. The results of this study discuss the absence of a gap between theory and the implementation of nursing care for clients 1 and 2 with effective cough exercises. This was shown from the results of interviews and observations of two clients with ineffective airway clearance problems based on the results of the assessment. Based on the implementation of nursing care, which had been carried out for 3 days, it was found that the problem had been resolved well. So the suggestion for future researchers is to increase research time so that they get maximum results.